The Effect of Earnings Quality to Bond Yields with Credit Risk as Moderating Variable - Ratna Candra Sari (Jurnal Akuntansi dan Bisnis, 2009)
Statement of Financial Accounting Concepts (SFAC) No. 1 (1978) has specified investors and creditors as the primary users of financial reporting. SFAC No.1 implies that earnings are useful to bondholders, but previous empirical research on the informativeness of earnings has focused on stock market rather than bond market. The objective of this research was to study the effect of earnings quality to bond yields and whether the effect of earnings quality to bond yields at high credit risk is higher than the effect of earnings quality to bond yields at low credit risk. Research has done in three years from 2001 to 2004. This is empirical research conducted on 82 corporate bonds chosen from a purposive sampling. The data obtained from the research are analyzed in a multiple regression analysis with interaction effects. The research finding show that the effect of earnings quality to bond yields was significant and the effect of earnings quality to bond yields at high credit risk is higher than the effect of earnings quality to bond yields at low credit risk. It is consistent with the hypothesis. Earnings quality is important to bondholders although bondholders was fixed claimant. This finding is important given the lack evidence about the usefulness of earnings quality to bondholders.